The role of mobile libraries in the County library network in the context of the acquisition of a new bookmobile for the "Fran Galović" Public Library Koprivnica (Libellarium: journal for research in the field of information and related sciences, 2024)
Aim. The paper aims to illustrate the development of the network of mobile libraries in Koprivnica-Križevci County, highlight the challenges in their development, operation, and funding, and emphasize the significance and importance of the existence of mobile library services in the County and the Republic of Croatia. Additionally, the aim is to describe the process of planning the construction and equipping of the new mobile library vehicle for the "Fran Galović" Public Library in Koprivnica, as well as the possibilities of developing programmes and services provided through the new vehicle.Approach/methodology/design. The research included an analysis of the legal framework for the establishment and operation of mobile libraries, research and analysis of existing statistical data, and reports on the activities of public libraries in Koprivnica-Križevci County and the mobile library service in Koprivnica. This paper outlines the process of developing a new mobile library vehicle, whose space and services were designed based on insights into the functioning of mobile services in Croatia and other European countries, obtained through research and the authors' direct insight into the work and development of mobile libraries.Results. The paper addresses the process and challenges of establishing, maintaining, and operating a network of mobile libraries in Koprivnica-Križevci County. It details the experience and challenges of purchasing, designing, construction, and equipping a new mobile library vehicle, as well as the development of programmes and services facilitated by the provision of new mobile library space.Originality/value. The experiences and examples presented in this paper are the result of the authors' many years of engagement and specialization in the field of mobile librarianship. The work synthesises professional knowledge acquired through practical work in the organization of mobile libraries, fieldwork in the mobile library itself, as well as gathering information and knowledge through training and direct observation of this segment of librarianship through personal insight into the work, equipment and programs in other countries. Consequently, the example of the establishment and operation of the mobile library service in Koprivnica, as an integral and extremely important part of the overall county network of public libraries in Koprivnica-Križevci County, and the experiences in the procurement, construction, and equipment of a new, modern mobile library vehicle presented in this paper, can serve as a very valuable source of information for other libraries planning to establish a mobile library service or to acquire a vehicle for its operation.
Keywords: bookmobile; mobile library; mobile library service; network of mobile libraries